ITIL Criteria for Developing a Monitoring Solution for e-Business Applications - Alexandru COCIORVA; Alexandru-Lucian VILCEA (Communications of International Proceedings, 2021)
The role of a monitoring solution in verifying and evaluating an e-business application is increasingly important in the context of the development of today's information society. Thus, the criteria chosen in the development of such an application must be relevant both to the e-business solution and to the context to which it belongs. Choosing a set of indicators as concrete as possible, as well as the accuracy of data resulting from the evaluation must provide a concise framework for substantiating decisions. Due to the fact that processes in ITIL framework are becoming an increasingly used component in evaluating e-business solutions, this paper aims to bring to the fore a working methodology which combines classical evaluation indicators with process indicators within the IPCC to substantiate the criteria for the development of a monitoring solution.
Keywords: Application; Monitoring; Evaluation; E-Business Solutions; ITIL; IPCC; Information Society; Methodology; Indicators